2013
DOI: 10.1371/journal.pone.0081562
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Pneumonia among Children Less Than Five Years with Acute Respiratory Symptoms in Mulago Hospital, Uganda: Evidence of Under-Diagnosis of Asthma

Abstract: BackgroundPneumonia is considered the major cause of mortality among children with acute respiratory disease in low-income countries but may be over-diagnosed at the cost of under-diagnosing asthma. We report the magnitude of asthma and pneumonia among “under-fives” with cough and difficulty breathing, based on stringent clinical criteria. We also describe the treatment for children with acute respiratory symptoms in Mulago Hospital.MethodsWe enrolled 614 children aged 2–59 months with cough and difficulty bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 35 publications
(68 reference statements)
1
57
2
1
Order By: Relevance
“…Pneumonia merupakan salah satu masalah kesehatan dan penyebab kematian anak usia di bawah lima tahun (balita) di dunia (Nantanda, Tumwine, Ndeezi, & Ostergaard, 2013). Di Indonesia, 23,8% kematian bayi disebabkan karena pneumonia dan 15,5% pada balita (Depkes RI, 2007), sehingga perlu upaya kesehatan dengan melibatkan keluarga dan masyarakat.…”
Section: Pendahuluanunclassified
“…Pneumonia merupakan salah satu masalah kesehatan dan penyebab kematian anak usia di bawah lima tahun (balita) di dunia (Nantanda, Tumwine, Ndeezi, & Ostergaard, 2013). Di Indonesia, 23,8% kematian bayi disebabkan karena pneumonia dan 15,5% pada balita (Depkes RI, 2007), sehingga perlu upaya kesehatan dengan melibatkan keluarga dan masyarakat.…”
Section: Pendahuluanunclassified
“…10 Prevalence of childhood asthma is substantial and asthma has often been treated as pneumonia and under-diagnosed in developing countries. 11 Bangladesh is no longer any exception of them with low prevalence. 12 Nevertheless, much of the data is extrapolated from geographical regions elsewhere with different demographics and there is paucity of epidemiological data on children admitted with respiratory complaints in the context of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs because the symptoms used to screen in pneumonia (cough and rapid breathing) coexist in asthma [59,60]. A recent study in Uganda [59] showed that 95 percent of 253 children with asthma syndrome received antibiotic treatments meant for pneumonia. These results are in line with a study in [61] where 46 percent of 200 children diagnosed with pneumonia (according to WHO criteria) actually had asthma.…”
Section: Background To the Researchmentioning
confidence: 99%
“…Currently, the diagnosis of pneumonia in resourcelimited settings relies on the guidelines developed by WHO and UNICEF, called the Integrated Management of Childhood Illness (IMCI) [55]. The implementation of IMCI revealed that asthma cases are often misdiagnosed as pneumonia [59,60]. The updated WHO guideline recommends the bronchodilator test to separate asthma from pneumonia; however, the test is costly, time consuming and rarely available in remote areas.…”
Section: Challenges In Pneumonia Managementmentioning
confidence: 99%
See 1 more Smart Citation